On λ D − R0 And λ D − R1 Spaces (2020)
In this paper we introduce the new types of separation axioms called λ D − R0 and λ D − R1 spaces, by using λ D-open set. The notion λ D − R0 and λ D − R1 spaces are introduced and some of their properties are investigated.